Evaluation of Cenchrus purpureus varieties with salinity tolerance in Valle del Cauto, Cuba. Agronomic performance - Álvarez Báez, Y.; Herrera, R. S.; Méndez Martínez, Y.; Ramírez de la Ribera, J. L.; Verdecia, D. (Cuban Journal of Agricultural Science, 2019)
Using a random block design and five replications (the experimental unit was the five-meter-long furrow), the evaluation of eight Cenchrus purpureus varieties obtained by in vitro tissue cultures with possible salinity tolerance (CT- 501, 502, 503, 504, 505, 506, 507 and 508) was performeddime and were compared with their progenitor (Cenchrus purpureus cv. Cuba CT-115). The experiment was developed in the Estación Experimental de Pastos y Forrajes (EEPF) belonging to the IIA "Jorge Dimitrov", Bayamo, Cuba. After the establishment cut, measurements every 15 days from 30 to 105 regrowth days were taken, in the rainy and dry seasons of the year. The analysis of the main components showed that the yield, leaf width, leaf area, length and width of the internode, leaves percent and height explain 93.14 % of the variability between varieties in the rainy season, while in the dry season the 86.12 % of the variability was explained through the width and length of the internode, length and width of leaves, leaves percent, yield and leaf area. The cluster analysis showed the presence of five and four groups of varieties for the periods mentioned, where the CT-508 is highlight for its higher height and yield. The multivariate analysis showed the agronomic indicators that most contribute to explain the variability among the varieties and it is suggested to deep into the bromatological indicators to develop management strategies for this region. Key words: multivariate analysis, forage, new varieties